The effects of different drying methods on the in vitro bioaccessibility of phenolics, antioxidant capacity, minerals and morphology of black 'Isabel' grape. (15th March 2022) - Ozkan, Kubra; Karadag, Ayse; Sagdic, Osman
Abstract: The black Isabel grapes were dehydrated by hot-air drying (HAD), vacuum-drying (VD), ultrasound-assisted vacuum-drying (US-VD), freeze-drying (FD), and their physical properties, phenolic compounds, antioxidant capacities, and mineral content were determined before and after simulated in vitro digestion. Among drying methods, FD provided the highest retention of the phenolic compounds, whereas US-VD caused the highest loss. The changes of phenolics of grapes differed among the digestion phases depending on the state of grapes (fresh or dried) and the drying method. The chlorogenic acid was the major phenolic compound identified, followed by protocatechuic acid and catechin. The malvidin-3- O- glucoside was the major anthocyanin followed by 3-glucosides of petunidin, delphinidin, cyanidin, and peonidin in the fresh and FD samples. At the end of digestion, a significant decrease in the levels of phenolics, minerals and no presence of anthocyanins was observed. VD raisins exhibited a higher bioaccessibility index for most of the phenolic compounds. Potassium was the most bioaccessible mineral from grape samples. Our results together with the morphology of the grapes revealed that different microstructures created by drying and the disruption of the natural matrix would influence the release, transformation, and subsequent absorption of phenolics and minerals in the simulated digestion model. Graphical abstract: Image 1 Highlights: The applied drying method was important for the bioaccessibility of phenolics. The morphology of fresh and dried grapes would influence the release of phenolics. None of the anthocyanins identified in fresh and dried grapes was bioaccessible. The potassium was the most bioaccessible mineral from grape samples.